LIVING QUR’AN DI MEDIA SOSIAL: RESEPSI Q.S AL-ASHR (1-3) DALAM FILM INSPIRASI “AL-QUR’AN MERINDUKANMU” PADA GONTOR TV - Anggraini, Tri Faizah (UIN Sunan Kalijaga Yogyakarta, 2024)
The study of the living Qur'an has now spread to cyberspace. The living Qur'an, which is generally synonymous with practical phenomena in real life, does not prevent the virtual world from taking part in representing the practice of the living Qur'an in the world of cinema. The same thing happened in the film